2022
DOI: 10.1002/mar.21671
|View full text |Cite
|
Sign up to set email alerts
|

The impact of socioeconomic status on preferences for sustainable luxury brands

Abstract: As consumers become more aware of and concerned about the environmental impact of their consumption choices, an increasing number of luxury brands are now engaging in sustainability practices. This study examines factors influencing the effectiveness of embedding sustainability in luxury brands. Specifically, the research focus is the effect of childhood socioeconomic status on moderating consumer preferences for sustainable (vs. regular, nonsustainable) luxury brands. Four experimental studies using different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 86 publications
(140 reference statements)
0
25
0
Order By: Relevance
“…In the case of luxury and fashion brands, sustainability undermines the perception of quality (Dekhili et al, 2019), esthetic appeal (Burke et al, 2014; Ramirez, 2013), trendiness (McNeill & Moore, 2015), and desirability (Sipila et al, 2020). Overall, luxury and sustainability are seen as incompatible (Dekhili et al, 2019; Sipila et al, 2020): luxury brands marketed as sustainable suffer from a lower brand attitude and decreased perceptions of luxury (Janssen et al, 2014; Kim et al, 2020).…”
Section: Results From the Thematic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of luxury and fashion brands, sustainability undermines the perception of quality (Dekhili et al, 2019), esthetic appeal (Burke et al, 2014; Ramirez, 2013), trendiness (McNeill & Moore, 2015), and desirability (Sipila et al, 2020). Overall, luxury and sustainability are seen as incompatible (Dekhili et al, 2019; Sipila et al, 2020): luxury brands marketed as sustainable suffer from a lower brand attitude and decreased perceptions of luxury (Janssen et al, 2014; Kim et al, 2020).…”
Section: Results From the Thematic Analysismentioning
confidence: 99%
“…Overall, luxury and sustainability are seen as incompatible (Dekhili et al, 2019;Sipila et al, 2020): luxury brands marketed as sustainable suffer from a lower brand attitude and decreased perceptions of luxury (Janssen et al, 2014;Kim et al, 2020).…”
Section: Product Perception Biasmentioning
confidence: 99%
“…Lastly, consumers' pursuit of sustainable consumption would depend on a lot of factors other than physical activity, such as their socioeconomic status (Kim et al, 2022), narcissism and faith in humanity (Bowen et al, 2022), generational cohort (Casalegno et al, 2022), and mindfulness (Kaur & Luchs, 2021). The integration of such consumer‐related factors that shape sustainable consumption along with physical activity should be pursued by future research.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Covid 19 pandemic has motivated stakeholders to share data (Viglia et al, 2021), and future research works may leverage on this understanding to request/collect consumer data on variables such as body mass index to assess the roles of such variables of salience (Bollimbala et al, 2019) in determining consumers' fitness and its impact on their consumption behaviors. Lastly, consumers' pursuit of sustainable consumption would depend on a lot of factors other than physical activity, such as their socioeconomic status (Kim et al, 2022), narcissism and faith in humanity (Bowen et al, 2022), generational cohort (Casalegno et al, 2022, and mindfulness (Kaur & Luchs, 2021). The integration of such consumer-related factors that shape sustainable consumption along with physical activity should be pursued by future research.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Previous research indicated that poverty or scarcity could impede human cognitive function [ 9 ], capturing attention with high resource demand and less susceptibility to other contexts [ 10 ]. Poverty could also play an important role in the decision-making area [ 1 , 8 , 11 , 12 , 13 ], such as marketing and purchase intention [ 4 , 6 , 14 ], sustainable choices [ 15 , 16 ], risk-taking [ 17 ], reproductive health [ 18 ], and loans [ 12 ].…”
Section: Introductionmentioning
confidence: 99%